PENGARUH REBUSAN DAUN SELEDRI DAN JUS MENTIMUN UNTUK MENURUNKAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS SIGALINGGING KAB. DAIRI - Heriaty Berutu; Rugun Togianur Lingga (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
WHO states that the blood pressure limit is 120-140 mmHg and systolic pressure is 80-90 mmHg. Hypertension is often found in developed societies, both men and women, old and young and the symptoms are not clearly visible. This disease is called silent diseases and is a major risk factor for the development or cause of heart disease and stroke. If not controlled, it will cause damage to other organs of the body, such as the brain, kidneys, and eyes and paralysis of the organs of movement. The purpose of the study was to determine the effect of celery decoction combined with cucumber juice to lower blood pressure in people with hypertension. The research method used a quantitative approach using Quasi Experimental Design where the experimental group and the control group were not selected randomly. In this design, both the experimental group and the control group were compared, although the group was selected and placed without going through random. The two existing groups were given a pretest, then given treatment, and finally given a posttest. The study population was all patients who had hypertension and who were treated in the Health Center Work Area. This study was conducted in the Sigalingging Health Center work area, Dairi Regency. The sample in the study were patients diagnosed with hypertension, which based on an initial survey, was found to be 44 people using data analysis techniques, univariate analysis and bivariate analysis with t-paired.